Necessary and sufficient conditions for quasi-strongly regularity of Graph Product - Do, Tuan Minh; Vu, Hoa Dinh (Journal of Computer Science and Cybernetics, 2018)
A $k$-regular graph ($k\ge 1$) with $n$ vertices is called a quasi-strongly regular graph with parameter $λ$ ($λ\in\NN$) if any two adjacent vertices have exactly $λ$ neighbors in common.A graph product is a binary operation on graphs. In this paper we prove some necessary and sufficient conditions for Decartes Product, Tensor Product, Lexicographical product and Strong product to be quasi-strongly regular.